A Contribution to „Semantic Hygiene“ in Political Theory and Practice (Czech Journal of International Relations, 1994)
"God or a nail, you either hang on God or on a nail," says T. G. Masaryk somewhere. For modern man, gradually losing the metaphysical certainty of faith in God, ideology was the most common substitute for "true", i.e. non-secular, religion, i.e. Masaryk's "nail".From the multitude of definitions of the word ideology, the basic attributes of this term can be "dissected". Ideology is a system of interrelated, more or less coherent ideas, opinions and beliefs by which a certain group of people identify themselves, the political environment in which they find themselves, their relationship to this environment and their role in it. Ideologies can mobilize and legitimize, but also mystify and manipulate. You can look for comfort or guidance in them. They often claim the right to normative arbitration. In their framework, terminological systems are often created, which serve both for communication within ideological entities and for spreading their beliefs externally.